Penerapan Asas Unus Testis Nullus Testis Oleh Hakim Dalam Membebaskan Terdakwa Dari Dakwaan Dan Upaya Hukumnya Oleh Jaksa - Rosadi, Rinaldi Yushar (Verstek, 2017)
This research is conducted to determine whether the application of the unus testis nullus testis  principle by the judges of Pengadilan negeri Menggala in the exemption of the accused from the charges of statutory rape and the legal remedies taken by the prosecutor is according to the principles of KUHAP or not.        As a legal research, this article is categorized as the normative legal research or doctrinal legal research. The approach used in this research is case approach. Legal Information used for this research are gathered by reading and studying documents, articles, and other literatures that contains the information regarding the case.        The result from the research shows that the usage of unus testis nullus testis principle by the judges of Pengadilan Negeri Menggala contradicted with the principles of KUHAP, the research shows that the testimony of the victim did not stand by its own. The judges declare that the other witnesses’ testimony that supported the victim’s testimony as irrelevant, even though the other witnesses’ testimony contains a clue to the case. The judges also disregard the visum et repertum that is also support the victim’s testimony. The research also shows that the legal remedies taken by the prosecutor is also contradicted with KUHAP principles, especially Article 244 which clearly said that cassation cannot be applied to acquittal, but that kind of action is taken for the good of the law itself.Keywords: Cassation, Unus Testis Nullus Testis Principle, Statutory Rape Crime